An Extensive Survey on Text Detection and Recognition - Garg, Sheetal; Akshatha, PS; Kavyashree, C (International Journal of Computer Sciences and Engineering, 2019)
This paper analyzes, compares, and contrasts the various methods in text detection and extraction. Existing techniques are categorized as either stepwise or integrated. Text detection and extraction can be categorized into sub-problems including text localization, verification, segmentation and recognition. It gives an elaborate view of the various methods applied for these sub problems. A number of benchmark datasets are discussed in details with their attributes.